2019
DOI: 10.2147/ott.s204340
|View full text |Cite
|
Sign up to set email alerts
|

<p>Microwave ablation compared with radiofrequency ablation for treatment of hepatocellular carcinoma and liver metastases: a systematic review and meta-analysis</p>

Abstract: Purpose Percutaneous ablation techniques, including microwave ablation (MWA) and radiofrequency ablation (RFA), have become important minimally invasive treatment options for liver cancer. This systematic review compared MWA with RFA for treatment of liver cancer. Methods The systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A systematic search of MEDLINE, EMBASE, and Cochrane Central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 58 publications
3
77
0
3
Order By: Relevance
“…The microwave antenna can be directly buried in the liver lesions under the B-ultrasound location. This treatment scheme has been proved to be safe and effective [5]. In the study of microwave ablation of liver cancer, many scholars [6] have proved that ≤5 cm of liver cancer can achieve therapeutic effect in recent years.…”
Section: Theoretical Basis Of Microwave Ablation Under Laparoscope 1)mentioning
confidence: 99%
“…The microwave antenna can be directly buried in the liver lesions under the B-ultrasound location. This treatment scheme has been proved to be safe and effective [5]. In the study of microwave ablation of liver cancer, many scholars [6] have proved that ≤5 cm of liver cancer can achieve therapeutic effect in recent years.…”
Section: Theoretical Basis Of Microwave Ablation Under Laparoscope 1)mentioning
confidence: 99%
“…97 Furthermore, in a meta-analysis that compared RFA and MWA for the treatment of hepatocellular carcinoma and liver metastases, the risk of local tumor progression was lower across all studies (risk ratio [RR] ¼ 0.70; p ¼ 0.02) as well as for randomized studies only (RR ¼ 0.55; p ¼ 0.007). 98 However, some studies have demonstrated higher complication rates following MWA likely due to higher temperatures. In a study that included 122 patients with 199 unresectable CRLM that were perivascular or peribiliary in location, overall severe complication rates (18.8 vs. 7.9%; p ¼ 0.09) and biliary complication rates following peribiliary ablation (57 vs. 3%; p ¼ 0.002) were higher for MWA compared with RFA.…”
Section: Microwave Ablationmentioning
confidence: 99%
“…Some systematically reviews and meta-analyses were performed to evaluate the efficacy of RFA and MWA in the treatment of HCC. [ 15 17 ] However, some meta-analyses included not only the primary liver cancer but also liver metastasis in their studies, which may led to a heterogeneity in the long-term outcome considering that metastasis is not representative of early stage tumors. [ 15 ] In addition, some studies enrolled patients who simultaneously underwent other treatments, such as transarterial chemoembolization (TACE), which may also be regarded as an incurable method for HCC, and resulted in decreased long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 17 ] However, some meta-analyses included not only the primary liver cancer but also liver metastasis in their studies, which may led to a heterogeneity in the long-term outcome considering that metastasis is not representative of early stage tumors. [ 15 ] In addition, some studies enrolled patients who simultaneously underwent other treatments, such as transarterial chemoembolization (TACE), which may also be regarded as an incurable method for HCC, and resulted in decreased long-term outcomes. [ 15 , 18 ] Moreover, most studies compared the survival outcome with living patients in each year, which may also represent a bias in assessing the impact of treatment due to lack of the “time-to-event” data.…”
Section: Introductionmentioning
confidence: 99%